Linking Entrepreneurship to Growth - Audretsch, David B.. (OECD Science, Technology and Industry Working Papers, 2001)
This paper provides a link between the degree of entrepreneurial activity in a country and the growth performance. While a recent wave of empirical evidence suggests that the extent to which countries have shifted towards an increased role of entrepreneurship varies considerably across countries, virtually nothing is known about the consequences of lagging behind in this process. Do countries that have shifted towards a greater role for entrepreneurship enjoy greater growth? This question is crucial to policy makers, because if the opportunity cost, measured in terms of forgone growth, of a slow adjustment towards a greater role for entrepreneurship is relatively low, the consequences of not engaging in a rapid adjustment process are relatively trivial. However, if the opportunity cost is high, the consequences are more alarming. This paper offers two distinct approaches, based on two different measures of entrepreneurship - the relative share of economic activity accounted for by ...